2015
DOI: 10.1161/circresaha.117.305781
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-103/107 Regulate Programmed Necrosis and Myocardial Ischemia/Reperfusion Injury Through Targeting FADD

Abstract: Rationale: Necrosis is one of the main forms of cardiomyocyte death in heart disease. Recent studies have demonstrated that certain types of necrosis are regulated and programmed dependent on the activation of receptor-interacting serine/threonine-protein kinase (RIPK) 1 and 3 which may be negatively regulated by Fas-associated protein with death domain (FADD). In addition, microRNAs and long noncoding RNAs have been shown to play important roles in various biological processes recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
179
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(193 citation statements)
references
References 54 publications
1
179
0
Order By: Relevance
“…Long non-coding RNA (lncRNAs) were characterized with the relatively stable style with their secondary structure in body fluids, thus, the detection of lncRNAs in human plasma or urine was possible for researchers [10][11][12]. Based on this, lncRNAs have been previously investigated for their potential role as cancer biomarkers in body fluids (either in plasma, serum or urine) [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNA (lncRNAs) were characterized with the relatively stable style with their secondary structure in body fluids, thus, the detection of lncRNAs in human plasma or urine was possible for researchers [10][11][12]. Based on this, lncRNAs have been previously investigated for their potential role as cancer biomarkers in body fluids (either in plasma, serum or urine) [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Myocytes injured during heart disease include both apoptotic and necrotic cells. Studies have shown that necrosis is more prominent in failing hearts and I/R hearts, which indicated that necrosis plays an important role in the pathological process of cardiac disease [11][12][13][14][15][16][17]. Oxidative stress is defined as an excess production of reactive oxygen species (ROS) relative to the endogenous antioxidant reserve to counteract the effects of ROS [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is defined as an excess production of reactive oxygen species (ROS) relative to the endogenous antioxidant reserve to counteract the effects of ROS [18][19][20][21][22]. Several studies have indicated that ROS induce the necrosis of cardiac myocytes and play a pivotal role in cardiac pathophysiology responsible for the development and progression of ischemic heart disease [17,23,24]. Nevertheless, the underlying mechanisms of cardiomyocyte necrotic death are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA NRF (Necrosis-Related Factor) was able to induce cardiomyocyte necrosis and exacerbate ischemia/reperfusion injury in H 2 O 2 -treated cardiomyocytes and myocardial infarction mice by sponging miR-873 and its target gene RIPK1 (Receptor-Interacting serine/threonine-Protein Kinase 1)/RIPK3 (Receptor-Interacting serine/threonine-Pro- [29].…”
Section: Nrf and H19 In Myocardial Necrosismentioning
confidence: 99%